The Role of the Regional Government of Boalemo Regency in Overcoming Mining Pollution Problems in the District of Pguyaman Pantai: Peran Pemerintah Daerah Kabupaten Boalemo dalam Mengatasi Masalah Pencemaran Pertambangan di Kecamatan Pguyaman Pantai - Pantika Maluyu (Universitas Negeri Semarang, 2022)
This research is a field research that uses data collection techniques by means of interviews, documentation and observation. This study aims to determine the impact on the people of Paguyaman Pantai District, especially the people of Limbatihu village as a result of continuous mining of pica stone and to understand the role of the government in overcoming pollution problems caused by pica mining companies in Paguyaman Pantai District. . This study uses descriptive qualitative. This study has two problem formulations, namely: first, what is the impact of environmental pollution by the pica stone mine in Paguyaman Pantai District? secondly, what is the role of the local government of Boalemo in overcoming the problem of environmental pollution from the pica stone mine in Paguyaman Pantai District? With the existence of the two main issues above, it can become a fundamental problem formulation in this research, so that the role of the Regional Government of Boalemo Regency in Overcoming Mining Pollution Problems in Pguyaman Pantai District is found, environmental pollution of the pica stone mine has troubled the surrounding community. The author really hopes that the regional government of Boalemo Regency will be able to overcome this pollution problem, protect the environment and create the health and welfare of the people in Paguyaman Pantai Subdistrict, especially the people of Limbatihu Village.